MAHASWETA DEVI AS A PUBLIC INTELLECTUAL: GLIMPSES OF RESISTANCE IN DRAUPADI - Nair, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Though India rejoices in the spell of chimerical prosperity, it is still mangled by the shackles of outmoded perceptions, oppression and attitudes of power. Over some time discrimination based on gender has been causing harrowing experiences to the women population weakening the social fabric. This high sense of insecurity, identity crisis and fragmentation felt within one’s own society paves the way for the bold intervention of academic and writer intellectuals bestowed with the special capability of strengthening and emancipating the lacerated section of the society. Many eminent writers of India came to the forefront as public intellectuals to articulate the traumatic experiences encountered by Indian women as the main subject in their narratives. Mahasweta Devi is one such writer who delineated the ceaseless exploitation and oppression faced by women and dared to make scathing comments about the unjust authority imposed on women making their lives deplorable. Through her writings, she explicitly manifested her growing concern for the oppressed and the exploited, rather victimised group. This paper attempts to examine the distinct traits that make Devi a renowned public intellectual and the imaginative ideas and ideologies manifested in her narratives that ignites the desperate urge among the victimised folk to look for ultimate solace. The paper further explores the gamut of unjust practices against subaltern women and the intriguing strategies of resistance in her celebrated short story Draupadi.